Materials about the relations of the Grand Duchy of Lithuania with the Crimean and Kazan Khanates in the years 1537–1538 from the Radziwiłł archive - Polekhov S.V.; Moiseev M.V. (Золотоордынское обозрение)
Research objectives: This article offers a source study and an edition of the missive of Khan Safa Giray of Kazan attached to the letter of King of Poland and Grand Duke of Lithuania Sigismund the Old (Zygmunt Stary) which he composent to the Council of Lords of the Grand Duchy of Lithuania on November 8, 1538. The research aims to contextualize the khan’s missive and to establish its date. Research materials: The copies of the letters preserved in the collection of Ignacy Onacewicz in the Institute of Russian Literature (Pushkin House) in St. Petersburg, as well as published subsidiary materials from the archival and library collections of Warsaw and Cracow. Results and novelty of the research: It is established that Safa Giray’s missive to Sigismund the Old, once kept in the Radziwiłłs’ archive, and now in Ignacy Onacewicz’s collection, was sent in the spring or summer/early autumn of 1538. It was preceded by a series of the khan’s missives to the king written during the year 1537 (this dating is substantiated) in the larger context of wars of the Russian State with the Grand Duchy of Lithuania (the Starodub War) and the Kazan Khanate, as well as the internal struggle in the Crimean Khanate. These missives are now preserved in Warsaw and Cracow. The texts of both missives from Ignacy Onacewicz’s collection, the khan’s missive to the king, and the king’s missive to the Council of Lords, are published for the first time.